Case report: A contralateral superficial cervical axial pattern flap in a large head and neck skin defect including a unilateral auricle - Gwan-Yong, Kim; Ho-Hyun, Kwak; Jun-Hyung, Kim; Heung-Myong, Woo (Frontiers in Veterinary Science, 2025)
A 3-year-old Shiba Inu was presented to the hospital with a large skin defect (15 cm × 25 cm, oval shape) on the head and neck, involving the left auricle, caused by a traffic accident. Necrotic tissue caused by inflammation was observed in the area of the skin defect. To address this condition, a sugar dressing was applied for 17 days to promote granulation tissue formation before performing a superficial cervical axial pattern flap. The flap was rotated by 120°, ensuring that the right superficial cervical artery remained undisturbed. The distal aspect of the flap was temporarily fixed to the forehead defect using a towel clamp before suturing. A 1 cm-long Penrose drain was pexied parallel to the vascular direction to reduce dead space. The grafted flap was adhered successfully without any significant complications. This case describes the successful treatment of a large head and neck skin defect, involving a sensory organ, using a contralateral axial pattern flap and Penrose drain pexy. This approach reduces the complications of axial-pattern flaps related to vascular twisting. Therefore, the use of contralateral superficial cervical axial pattern flap and Penrose drain pexy may be an effective solution for large head and neck skin defects, including auricular defects.